Pharmacological Ureteral Dilation With İntraluminal Papaverine Administration - Gunes, Ali; Zengin, Tahir; Yilmaz, Ugur; Soylu, Ahmet; Ugras, Y.Murat; Derya Balbay, M. (Annals of Medical Research, 2021)
None
Keywords: Ureter, Papaverin, Dilatation